2022
DOI: 10.1097/pgp.0000000000000837
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Leiomyosarcoma Associated With Leiomyoma With Bizarre Nuclei: Histology and Genomic Analysis of 2 Cases

Abstract: Leiomyoma with bizarre nuclei (LM-BN) is a rare variant of leiomyoma with overall benign clinical course. It has histologic features showing focal or diffuse nuclear atypia surrounded by usual type leiomyoma. Uterine leiomyosarcomas (LMS) are a group of rare and aggressive malignancies with limited treatment options available. The potential association between LM-BN with LMS is largely unknown. In this study, we report 2 cases of uterine smooth muscle tumor with typical histologic and molecular evidence of LM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…10 , 48 Increasing evidence shows that LBN may represent a potential stage of malignant tumor progression. 17 , 72 Therefore, it is necessary to prevent the spread of tumor cells. For recurrent LBN, hysterectomy is the treatment of choice for patients that have completed their families and follow-up imaging should be carried out at least once a year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10 , 48 Increasing evidence shows that LBN may represent a potential stage of malignant tumor progression. 17 , 72 Therefore, it is necessary to prevent the spread of tumor cells. For recurrent LBN, hysterectomy is the treatment of choice for patients that have completed their families and follow-up imaging should be carried out at least once a year.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 , 21 Recently, Fischer et al reported two cases of LBN that progressed to LMS. 17 Furthermore, molecular genetic studies have suggested that the morphological changes in LBN most likely reflect severe genomic abnormalities instead of simple degenerative alterations, which may represent a potential malignant stage of precancerous progression. 16 , 48 , 51 However, large-scale clinical trials are needed for further verification.…”
Section: Different Diagnostic Tools For Lbnmentioning
confidence: 99%
See 2 more Smart Citations
“…The differential diagnosis of uterine IMT. [15][16][17][18][19] so far, [23] and cases are needed to summarize the optimal management of uterine IMT.…”
Section: Tablementioning
confidence: 99%